Development of Teaching Materials Based on Fullan's Deep Learning Framework to Improve the Creative Thinking of Grade VI Elementary Students in Palopo City - Putri, Iin Dwi Aristy; Akib, Erwin; Munirah, Munirah (PPSDP International Journal of Education, 2025)
This study aims to develop teaching materials based on the pedagogical framework of Deep Learning. In the era of globalization and the industrial revolution 4.0, creative thinking as a 21st century skill is crucial, but students experience a "creativity crisis" due to the dominant memorization approach. Initial observations showed a low Torrance Tests of Creative Thinking as fluency, flexibility, and originality in Palopo, influenced by Bugis-Makassar cultural factors and limited resources. The research method used a systematic literature following PRISMA guidlines, analyzing 50 sources from the journal Scopus, the national journal SINTA, and seminar proceedings (2015-2025). Thematic analysis resulted in themes of deep learning concepts (Fullan, 2018), creativity indicators (Torrance, 1974), teaching material design, and implementation challenges. The results showed that deep learning with aware, meaningful, and encouraging elements increased creativity by up to 35% through thematic modules based on local culture, such as Bugis folklore and oil palm waste management projects. The ADDIE framework is proposed for development, in line with the Independent Curriculum. These teaching materials have the potential to address the stagnation of creativity, with recommendations for teacher training and contextual adaptation for replication in eastern Indonesia.